2003
DOI: 10.1103/physreve.67.061201
|View full text |Cite
|
Sign up to set email alerts
|

Scaling behavior for the pressure and energy of shearing fluids

Abstract: Recent simulation work has established that the widely accepted mode-coupling theory for the strain rate dependence of the pressure and energy of simple fluids under shear (i.e., energy and pressure are functions of strain rate to the power 3 / 2) is observed in the vicinity of the triple point. Away from the triple point, the scaling exponent of the strain rate was seen to be closer to 2 than 3 / 2, suggesting a possible analytic behavior. In this paper, we accurately determine the scaling exponent behavior f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 9 publications
4
30
0
Order By: Relevance
“…Data published by Ge et al [19] are consistent with our results. They showed that for a dense LJ liquid under shear flow, the potential energy and the pressure can be fitted by a power-law dependence on strain rate, U = U 0 + aγ α (31)…”
Section: Figsupporting
confidence: 83%
See 1 more Smart Citation
“…Data published by Ge et al [19] are consistent with our results. They showed that for a dense LJ liquid under shear flow, the potential energy and the pressure can be fitted by a power-law dependence on strain rate, U = U 0 + aγ α (31)…”
Section: Figsupporting
confidence: 83%
“…They found [19] that the linear expression α = A + BT − Cρ represents well their simulations with A = 3.67, B = 0.69, and C = 3.35. To make a connection between these results and isomorph theory, recall that the collapse seen in Fig.…”
Section: Figmentioning
confidence: 90%
“…An alternative analysis of the density dependence of the pressure versus shear rate data has been presented by Ge et al [15]. They fitted a power law to the pressure versus shear rate data for an atomic fluid over a fixed range of shear rates, allowing the exponent to vary with density.…”
Section: Resultsmentioning
confidence: 98%
“…Apart from a few detailed computational investigations for atomic fluids [27,28], this equation of state has received little attention, but it is possible to obtain one from the retarded motion expansion. Most derivations of the retarded motion expansion introduce the incompressibility assumption at an early stage [11,12,29], but it is possible to carry out the derivation without making this assumption.…”
Section: Retarded Motion Expansion For a Compressible Fluidmentioning
confidence: 99%